Application of scenario-driven hazard analysis in the solid rocket booster - Jenab, Kouroush; Ottosen, Nikita; Moslehpour, Saeid (International Journal of Engineering and Technology, 2016)
Bibliographical Notes: Kouroush Jenab is a senior member of IEEE, received the B.Sc. degree from the IE Department at Isfahan University of Technology (1989), the M.Sc. degree from the IE Department at Tehran Polytechnic (1992), and the Ph.D. degree from the Department of Mechanical Engineering at the University of Ottawa (2005). He served as a senior engineer/manager in auto, and high-tech industries for 18 years. He joined the National Research Council Canada as a research officer where he participated in several international research projects. In 2006, he joined the Department of Mechanical and Industrial Engineering at Ryerson University, Toronto as assistant professor. Currently, Dr. Jenab is Faculty of the College of Aeronautics at Embry-riddle Aeronautical University, FL, USA. He has published over 110 papers in international scientific journals based on his experiences in industries.Nikita Ottosen is a current Systems Engineering graduate student at Embry-Riddle Aeronautical University. She received her undergraduate degree from ERAU in Aeronautics and is currently working as an Assistant Campus Director at the Crestview, FL campus. She gained valuable knowledge previously working for the Boeing Company and Seattle-Tacoma International Airport, known as The Port of Seattle, in Seattle, Washington. During her time at The Port of Seattle she worked alongside the Wildlife Management department to conduct a study on effective wildlife management strategies. Her study will become a part of a future Airport Cooperative Research Program (ACRP) publication, sponsored by the FAA’s Transportation Research Board of the National Academies.Saeid Moslehpour is a full professor and department chair in the Electrical and Computer Engineering Department in the College of Engineering, Technology, and Architecture at the University of Hartford. He holds Ph.D. (1993) from Iowa State University and Bachelor of Science (1989) and Master of Science (1990) degrees from University of Central Missouri. His research interests include failure analysis, logic design, CPLDs, FPGAs, Embedded electronic system testing and distance learning.